2020
DOI: 10.1007/s00432-020-03335-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical responses to PD-1 inhibition and their molecular characterization in six patients with mismatch repair-deficient metastatic cancer of the digestive system

Abstract: Purpose Immune checkpoint inhibitors have shown efficacy in patients with microsatellite instability-high/mismatch repair-deficient (MSI-H/dMMR) gastrointestinal (GI) cancers. However, depth and duration of clinical response is not uniform. We assessed tumor mutation burden (TMB) as a response marker in patients with GI cancers treated with immune checkpoint inhibitors. Methods Detailed clinical and response data were collected from six patients with metastatic MSI-H/dM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…MSI-H tumors tend to have high tumor mutational burden (TMB), and studies have demonstrated that TMB is commonly increased in MSI-H mCRC, but still unclear (54). In mCRC patients treated with durvalumab and tremelimumab, OS is the greatest in MSS Patients with more plasma TMB of 28 variants per megabase or more (HR, 0.34; 90% CI, 0.18-0.63; P = .004) ( 37 (57). By comparing the expression of 44 selected immune-related genes in the primary colon tumor between responders (n = 13) and nonresponders (n = 6) after anti-PD-1 therapy, Llosa et al concluded that preexisting antitumor immune response has little predictive value for immunoreactive pMMR CRC (58).…”
Section: Biomarkers Of Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…MSI-H tumors tend to have high tumor mutational burden (TMB), and studies have demonstrated that TMB is commonly increased in MSI-H mCRC, but still unclear (54). In mCRC patients treated with durvalumab and tremelimumab, OS is the greatest in MSS Patients with more plasma TMB of 28 variants per megabase or more (HR, 0.34; 90% CI, 0.18-0.63; P = .004) ( 37 (57). By comparing the expression of 44 selected immune-related genes in the primary colon tumor between responders (n = 13) and nonresponders (n = 6) after anti-PD-1 therapy, Llosa et al concluded that preexisting antitumor immune response has little predictive value for immunoreactive pMMR CRC (58).…”
Section: Biomarkers Of Immune Responsementioning
confidence: 99%
“…However, based on the clinical response data collected from six patients with metastatic MSIH/DMMR GI cancers treated by ICIS, Hirsch et al. found that TMB wasn’t associated with extent and duration of response ( 57 ). By comparing the expression of 44 selected immune-related genes in the primary colon tumor between responders (n = 13) and nonresponders (n = 6) after anti-PD-1 therapy, Llosa et al.…”
Section: Immune Checkpoint Inhibitors Therapymentioning
confidence: 99%
“…Various diagnostic methods including endoscopic ultrasound (EUS), magnetic resonance imaging (MRI), computed tomography (CT), ultrasound (US), and positron emission computed tomography (PET) are routinely used to identify malignancies [3][4][5]. These imaging techniques assist doctors in evaluating and examining the digestive system, thereby pinpointing the precise location and segmented sections of the cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To date, immune checkpoint inhibitors (ICIs) have become a crucial therapeutic option for improving prognosis in several solid tumors [4,5]. Previous clinical trials have shown that microsatellite instability (MSI) and/or mismatch-repair deficiency (dMMR) constitute significant tissue-agnostic molecular markers for the prediction of ICIs' efficacy [6][7][8][9]. Because genetic and immunohistochemical (IHC) tests for MMR deficiency are available, pem-brolizumab and nivolumab as monotherapies or combined with ipilimumab have had approval from the US Food and Drug Administration (FDA) for treating chemoresistant MSI/dMMR mCRC cases [10].…”
Section: Introductionmentioning
confidence: 99%